Differential Cry toxin detection and effect on Brevicoryne brassicae and Myzus persicae feeding on artificial diet. Issue 1 (11th March 2016) - Paula, Débora P.; Andow, David A.
Abstract: The literature about effects of genetically modified plants expressing Cry toxins has several contrasting results regarding detection and effects of Cry toxins on aphids. To test the hypothesis that this variation could be due to a lack of controlled exposure, and not just a lack of toxicity, we used an artificial aphid rearing system to detect acquisition and examine potential effects of Cry1Ac and Cry1F on mortality and population growth rate of cabbage aphid, Brevicoryne brassicae (L.), and green peach aphid, Myzus persicae (Sulzer) (both Hemiptera: Aphididae). Using enzyme‐linked immunosorbent assay (ELISA), Cry1Ac and Cry1F were not detected in B. brassicae feeding on any of the Cry diets, whereas in M. persicae, Cry1Ac was detected in 55% of samples exposed alone or in combination with Cry1F, and Cry1F was detected in 67% of samples exposed alone or in combination with Cry1Ac. The toxins reduced the net population growth rate of M. persicae, but not of B. brassicae . For M. persicae, the reduction in growth rate was similar for Cry1Ac and Cry1F and there was no synergism from co‐feeding the aphids with both Cry toxins. The toxins had no detectable effect on survival of either aphid species. Variability in detection and effects of Cry toxins on aphids may not depend only on the presence and level of a Cry toxin in the phloem, and on differential experimental conditions as previously suggested, but may also depend on some characteristic of the aphid that remains to be determined.